Formal (4+1) Cyclization of Ammonium Ylides with Vinylogous para-Quinone Methides - Roiser, Lukas; Zielke, Katharina; Waser, Mario (Synthesis, 2018)
The formal (4+1) cyclization between in situ generated achiral carbonyl-stabilized ammonium ylides and vinylogous p-quinone methides can be carried out under operationally simple conditions, leading to two different double bond regioisomers depending on the conditions used. Apart from these racemic approaches, a first proof-of-concept for enantioselective versions of these reactions was also obtained.
Keywords: ammonium ylides; quinone methides; cyclization; regioisomers; stereoselectivity